DESENVOLVIMENTO, ESTABILIDADE E ATIVIDADE ANTIOXIDANTE DE CARREADORES LIPÍDICOS NANOESTRUTURADOS CONTENDO QUERCETINA E AVALIAÇÃO DO EFEITO CITO-GENOTÓXICO IN VITRO - Mussoi, Thiago Durand (2019)
The Food Bioactive Compounds (FBC) present biological activities which can result in benefits to human health as antioxidant, anti-inflammatory, antimutagenic, hypolipidemic activities, and others. Among the FBC, the compounds of Phenolic Bioactive Compounds (PBC), present at high levels in the plant origin food, are associated to the lower incidence of chronic diseases. In the several PBCs, there are the flavonoids, specially, the quercetin. This bioactive compound has shown diverse nutraceutical activities with emphasis to the antioxidant activity. However, the oral bioavailability of quercetin is limited, mainly because of its weak aqueous solubility and poor intestinal permeability. Thus, the incorporation of quercetin in nanostructured release systems, mainly, the lipidic nanocarriers, can be considered a promising alternative for the oral administration of this compound. The objective of the current work was to develop, characterize and validate the analytical method of the Nanostructured Lipid Carriers containing Quercetin (NLC-Q) and to verify the stability through the physio-chemical analysis, antioxidant activity, and their effects in the cytotoxicity and genotoxicity in cellular pattens. The production methods of NLC-Q, was of a high rate of shearing, a method that has presented itself as efficient as nanoparticles were obtained with sizes of 111.7 ± 1.19 nm, PDI of 0.18 ± 0.009, zeta potential of -9.18 ± 2.34 mV and pH of 5.73 ± 0.08, characterization done with dynamic light mirroring. The efficiency of encapsulation and levels of NLC-Q were respectively 100% and 99.58 ± 0.21%. The analytical method for the quercetin quantification was developed and validated with the High Performance Liquid Chromatography of High Performance (HPLC). This method has proved as linear, specific, precise, accurate and robust for the determination and quantification of quercetin. The toxicologic evaluation of NLC-Q and its constituents, face the human fibroblasts (HFF-1 ATCC®) and Peripheral Blood Mononuclear Cells (PBMC) in different concentrations (10; 50 and 100 μg/mL), has shown that, in general, the NLC-Q, Quercetin (Q) and Tensioactives (T) do not present cytotoxicity, in the cellular pattern of human fibroblasts, as well as there was no cytotoxicity in the PBMC during the time analyzed. In addition, there was no genotoxicity of NLC-Q with the Picogreen® method. In the evaluation of physio-chemical stability of NLC-Q in different storage conditions, during 180 days, it was verified, by and large, the maintenance of the average diameter and the polydisperse index of NLC-Q; meanwhile, there were meaningful alterations in the zeta potential and in the pH. The assessment of the antioxidant activities in different storage conditions, also by the period of 180 days, was realized with the Folin-Ciocalteu method, DPPH and ABTS. Broadly, it was verified a gradual diminishing of the antioxidant activity of the nanostructured quercetin in the period evaluated (180 days). Although, there was meaningful difference when comparing the nanostructured quercetin with the free quercetin, that is, the nanostructured quercetin had its antioxidant action better preserved in relation to the free quercetin. It was also observed that the refrigerated environment was the best storage condition for the NLC-Q as for the maintenance of the physio-chemical characteristics and for the antioxidant activity. Based on the results obtained, it is concluded that the NLC-Q presented adequate physio-chemical stability, in general, they did not present cyto-genotoxicity for the PBMC, as they also presented a significant maintenance of the antioxidant activity, when compared to the non- nanostructured quercetin. Yet, it is highlighted the importance of new experiments, mainly concerning the antioxidant activity to validate the findings, as well as for the additional tests relating to the in vitro and in vivo safety profile.